HAM‐2 and HAM‐3 are central for the assembly of the Neurospora STRIPAK complex at the nuclear envelope and regulate nuclear accumulation of the MAP kinase MAK‐1 in a MAK‐2‐dependent manner. Issue 4 (1st October 2013) - Dettmann, Anne; Heilig, Yvonne; Ludwig, Sarah; Schmitt, Kerstin; Illgen, Julia; Fleißner, Andre; Valerius, Oliver; Seiler, Stephan
Summary: Intercellular communication and somatic cell fusion are important for fungal colony establishment, multicellular differentiation and have been associated with host colonization and virulence of pathogenic species. By a combination of genetic, biochemical and live cell imaging techniques, we characterized the Neurospora crassa  STRIPAK complex that is essential for self‐signalling and consists of the six proteins HAM‐2/STRIP, HAM‐3/striatin, HAM‐4/SLMAP, MOB‐3/phocein, PPG‐1/PP2A‐C and PP2A‐A. We describe that the core STRIPAK components HAM‐2 and HAM‐3 are central for the assembly of the complex at the nuclear envelope, while the phosphatase PPG‐1 only transiently associates with this central subcomplex. Our data connect the STRIPAK complex with two MAP kinase pathways: (i) nuclear accumulation of the cell wall integrity MAP kinase MAK‐1 depends on the functional integrity of the STRIPAK complex at the nuclear envelope, and (ii) phosphorylation of MOB‐3 by the MAP kinase MAK‐2 impacts the nuclear accumulation of MAK‐1. In summary, these data support a model, in which MAK‐2‐dependent phosphorylation of MOB‐3 is part of a MAK‐1 import mechanism. Although self‐communication remained intact in the absence of nuclear MAK‐1 accumulation, supporting the presence of multiple mechanisms that co‐ordinate robust intercellular communication, proper fruiting body morphology was dependent on the MAK‐2‐phosphorylated N‐terminus of MOB‐3.